Implementação de algoritmo metaheurístico simulated annealing para problema de seleção de contingência em análise de segurança de redes elétricas - Tomazi, Fausto Stefanello (Universidade do Vale do Rio dos Sinos, 2016)
Power systems play a key role in a nation's economy by providing quality, uninterrupted power to the population. For this to be possible large investments in the sector are applied to guarantee the supply. However, any equipment is subject to failures, and analyzing the impact that equipment failures affect supply is one of the tasks performed by control centers, called Safety Analysis. In this way, the control centers are responsible for carrying out contingency plans so that in the event of any equipment leaving the operation the impact suffered by the network is as small as possible. An important task of Security Analysis is the Selection of Contingencies. This task is in charge of selecting the most important equipment in the system so that the Security Analysis task can create prevention plans if the respective equipment goes out of operation. The large electrical systems that exist today are made up of thousands of equipment, and a more detailed analysis for each equipment is difficult to solve, and in this scenario contingency selection is important. The Contingency Selection is responsible for searching and classifying the most important restrictions of the network, but for large networks with thousands of items, analyzing the impact of each item is a task that can take a long time, not allowing the calculation to be performed During system operation. In this way it is necessary to perform the Contingency Selection efficiently and effectively. This study proposes the development of the metaheuristic algorithm of Simulated Annealing in order that the contingency selection is performed in a way that meets all the time constraints imposed by the control centers. In the experiments it is possible to verify that after a tuning of parameters for the instance of the problem approached, the results found meets the control center constraints and it is also possible to visualize that the results are slightly better than results of works found in the literature, where the same Problem is addressed by the metaheuristic of the Genetic Algorithm.
Keywords: Simulated annealing; Análise de segurança; Metaheurística; Sistemas de potência; Análise de segurança; Fluxo de potência; Security analysis; Metaheuristic; Grid power systems; Security of power systems; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação